The Role of Behavioral Measures in Accounting for Human Resources: A Reply. - Dermer, J. D.; Siegel, J. P. (The Accounting Review, 1975)
Presents a response to a letter to the editor regarding the role of behavioral measures in accounting for human resources, published in this issue of the periodical.